Endoscopic injection of autologous blood for bleeding gastroduodenal ulcers - Schneider, A.; Schepp, W. (Endoscopy, 2011)
Endoscopic injection of diluted epinephrine and the application of endoclips or thermal probes are established endoscopic therapies for peptic ulcer bleeding (PUB). However, autologous blood may offer advantages at least over diluted epinephrine due to its specific properties: corpuscular components may provide prolonged persistence and procoagulatory constituents may additionally prevent recurrent bleeding. We performed successful endoscopic injection of autologous blood for acute spurting (Forrest Ia) or oozing (Ib) bleeding from duodenal or gastric ulcers. The injection of autologous blood was simple to apply and achieved hemostasis in bleeding Forrest I peptic ulcers. This technique can be considered as an adjunct or an alternative to other methods for endoscopic control of PUB.